Strategies of Islamic Religious Education Teachers in Integrating Ngasa Local Traditional Values into Elementary School Learning - Ahmad Abdul Rochim; Sukiman Sukiman; Zainal Arifin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to analyze the integration of Ngasa traditional values into Islamic Religious Education (IRE) learning at SDN 2 Cisereuh, Brebes Regency, and to identify the strategies, supporting factors, and inhibiting factors involved in the process. The study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving IRE teachers, the school principal, and Jalawastu traditional leaders. Data were analyzed using the interactive model of Miles and Huberman, consisting of data condensation, data display, and conclusion drawing. The findings reveal that IRE teachers integrate Ngasa traditional values, particularly togetherness, mutual cooperation (gotong royong), and deliberation (musyawarah), into learning materials, learning processes, teaching materials, and instructional media. These values are contextualized with Islamic teachings, enabling students to understand religious concepts through their socio-cultural experiences. The integration process is supported by students’ enthusiasm, parental support, community participation, and teachers’ understanding of local cultural values. However, several challenges remain, including the limited availability of local culture-based learning resources, the absence of local cultural content in the curriculum, and insufficient professional development related to local wisdom-based learning. This study concludes that the Ngasa tradition serves as a relevant and meaningful source of values for strengthening Islamic Religious Education while contributing to the preservation of local cultural heritage.